(untitled) (Економіка і регіон/ Economics and region, 2024)
The level of competitiveness should be at a satisfactory level in order to achieve the main goals of enterprises in the conditions of competitive struggle - to achieve certain results. In modern economic literature, economists approach the concept of the competitiveness of enterprises from different positions, but they agree on one issue that it is possible to manage the competitiveness of enterprises and this process must be managed. In many countries of the world, construction companies can be shown as highly profitable enterprises that develop economically in a favorable environment. The existence of a construction market is the main financial condition for meeting the human demand for housing. Every company, from the time of its establishment and throughout its existence, should strive to effectively manage the organization so that their enterprises and organizations can gain a superior competitive position in the market. Because, in the conditions of competitive struggle, enterprises are not only fighting to stay afloat, the main goal of any commercial organization is to obtain and increase profits. The current economic conditions in the Republic of Azerbaijan are characterized by high development rates and the strengthening of market economy relations, as well as integration processes at the domestic and international levels. The competitive environment in the construction industry has its own characteristics, which reflect the regional nature of the competitive struggle and are manifested in contract trades. Here we are talking about the dominance of price competition in the field. In such an aspect, it would be appropriate to pay attention to the content of the concept of competitiveness in the environment in which construction organizations operate in modern times. Competitiveness management refers to methods of finding, selecting, supporting, using and developing competitive advantages. In the article, the characteristics of the competitive environment in the construction industry were investigated, and the system of evaluation methods of competitiveness management was comparatively characterized.